Sulfonamide Residues: Honey Quality in the Czech Market - Sandra Dluhošová; Ivana Borkovcová; Lenka Kaniová; Lenka Vorlová (Journal of Food Quality)
In this study, we determined four sulfonamide compounds (sulfadiazine, sulfadoxine, sulfamethoxazole, and sulfathiazole) in honey marketed in the Czech Republic (Brno). The content of these compounds was monitored in 50 honeys with different botanical and geographical origin. Preanalytical treatment included acidic hydrolysis with 10% trichloroacetic acid (TCA) and double extraction with acetonitrile and dichloromethane. Chromatographic analysis was performed by ultraperformance liquid chromatography with tandem mass spectrometry (UPLC-MS/MS) using a triple quadrupole (QqQ) in positive ionization mode (ESI+). For separation, the mobile phase was a 0.05% aqueous solution of formic acid (A) and 0.05% formic acid in methanol (B) with a gradient elution of 0–3 minutes: 10% B; 3–3.6 min: 90% B; and 3.6–5 min: 10% B, flow rate 0.30 ml/min. Three positive samples (6%) were found containing sulfadiazine (232.88 and 618.87 μg/kg) and sulfamethoxazole (62.64 μg/kg). According to the country of origin, two of these honeys were from European Union (EU) countries, and one was labeled as a blend of honey from EU and non-EU countries.